TO UNDERSTAND, TO FEEL AND TO APPROPRIATE: THE SOUTH KOREAN TELEVISION SERIES “MOON LOVERS— SCARLET HEART: RYEO” IN DISCUSSIONS OF RUSSIAN—SPEAKING VIEWERS / ПОНЯТЬ, ПРОЧУВСТВОВАТЬ И ПРИСВОИТЬ: ЮЖНОКОРЕЙСКИЙ СЕРИАЛ «ЛУННЫЕ ВЛЮБЛЕННЫЕ — АЛЫЕ СЕРДЦА: КОРЁ» В ОБСУЖДЕНИЯХ РУССКОЯЗЫЧНЫХ ЗРИТЕЛЕЙ - TARASOVA A.V. / ТАРАСОВА А.В. (Наука телевидения)
The article aims to explore some aspects of the reception of South Korean serials by Russian-speaking viewers. One of the results of the “Korean wave” has been the growing popularity of Korean Television Series around the world; there are plenty of online resources today which allow viewers abroad to watch them and participate in discussions of them—in different languages, including Russian. The main source for this study is the users’ forum on the Russian site DoramaTV, where “Moon Lovers: Scarlet Heart Ryeo” has been discussed for almost three years. This television series, (a mixture of fantasy, love story and historical narrative) did not have much success in the Republic of Korea, but won the love of an international audience. Analysis of the discussion of the television series on the forum makes it possible for us to discern some of the characteristics of their involvement. Viewers were able to overcome the historical and cultural obstacles as the result of their previous experience of watching Korean historical series and to their coordinated efforts to find the information they needed. Most of all, the fans appreciated the power of the story to evoke strong feelings in them—both joy and tears; the “foreignness” of the characters did not provide a drawback for the viewers to sincere empathy, both on an individual and a collective level. Disappointed by the low viewing figures in Korea, the viewers attempted at every opportunity to make their voices heard by the crew and the television channel management; they participated in online voting and signed petitions to extend the show for a second season. And although their hopes for continuation were frustrated, the viewers still retained a mostly enthusiastic attitude toward the series, which they eventually came to regard as something to which they had at least the same rights as the Korean audience, as something that was “their own.”